ATIVIDADE LARVICIDA SOBRE Aedes aegypti L. (Culicidae) E COMPOSIÇÃO QUÍMICA DO ÓLEO ESSENCIAL DE PARTES AÉREAS DE Baccharis trimera (Less) D.C. - SILVEIRA, Daniella Patrícia Brandão (2018)
Mosquito-borne diseases still persist as an important global health problem. Aedes aegypti is one of the main vectors of diseases transmitted by mosquitoes, such as Yellow Fever, Dengue, Zika, Chikungunya; arboviruses that can lead to hemorrhagic shock, embryonic malformations, joint diseases and death Thus, one of the ways recommended by the World Health Organization for the control of arboviruses is the vector control, the mosquito Aedes aegypti. In this sense, there is a tendency to search for natural products that can be used as potential larvicides and insecticides. In this context, the objective of this work was to evaluate the chemical composition of Baccharis trimera (Less) DC and to verify if it presents activity against larvae of the Aedes aegypti vector and evaluate the toxicity of the product against non-target organizations. Plant material was obtained from the Multidisciplinary Center for Chemical, Biological and Agricultural Research - CPQBA of the State University of Campinas - UNICAMP. A sample was sent to the Herbarium of the Federal University of Maranhão, to confirm the species. The essential oil was extracted by hydrodistillation and the identification of the chemical compounds was obtained by Gas Chromatography coupled to Mass Spectrometry. It was possible to identify 90% of the substances present in the essential oil under study, being 10% composed of hydrocarbon monoterpenes, 14% of oxygenated monoterpenes, 24% of oxygenated sesquiterpenes and 45% of hydrocarbon sesquiterpenes. The essential oil in this study had as its major compounds spatulenol (18.45%), caryophyllene oxide (15.24%) and e-caryophyllene (9.18%). The evaluation of larvicidal activity was performed for the four larval stages (L1, L2, L3, L4) at six concentrations. Cytotoxicity tests against Artemia salina and Danio rerio were performed and the respective LC's50 were calculated. It is considered that the essential oil of Baccharis trimera is effective against larvae between the 1st and 4th stage of Aedes aegypti, it was obtained LC's50 equivalent to 38.8; 55.8; 89.7; 171.8 μg / mL for 1st, 2nd, 3rd and 4th stages, respectively. The oil may be considered toxic for Danio rerio, however it was non-toxic or of low toxicity in a toxicity test against Artemia salina.